Proximate Analysis of Five Wild Fruits of Mozambique - Telma Magaia; Amália Uamusse; Ingegerd Sjöholm; Kerstin Skog (The Scientific World Journal)
Mozambique is rich in wild fruit trees, most of which produce fleshy fruits commonly consumed in rural communities, especially during dry seasons. However, information on their content of macronutrients is scarce. Five wild fruit species (Adansonia digitata, Landolphia kirkii, Sclerocarya birrea, Salacia kraussii, and Vangueria infausta) from different districts in Mozambique were selected for the study. The contents of dry matter, fat, protein, ash, sugars, pH, and titratable acidity were determined in the fruit pulps. Also kernels of A. digitata and S. birrea were included in the study. The protein content in the pulp was below 5 g/100 g of dry matter, but a daily intake of 100 g fresh wild fruits would provide up to 11% of the recommended daily intake for children from 4 to 8 years old. The sugar content varied between 2.3% and 14.4% fresh weight. The pH was below 3, except for Salacia kraussii, for which it was slightly below 7. Kernels of A. digitata contained, on average, 39.2% protein and 38.0% fat, and S. birrea kernels 32.6% protein and 60.7% fat. The collection of nutritional information may serve as a basis for increased consumption and utilization.